Challenges faced by English Language Teachers in teaching Present Indefinite Tense to Primary Learners - Jabeen, Sehrish; Zahid, Zohaib; Ramzan, Sadia (Annals of Human and Social Sciences, 2024)
The present study is an investigation on the challenges faced by EFL teachers in teaching Present indefinite tense in Primary schools. It is exploratory in nature and was organized by using some characteristics of the mixed method research design. EFL teachers encounter various challenges in teaching primary students the Present Indefinite Tense. Firstly, the abstract nature of tense concepts can be difficult for young learners to grasp. Secondly, cultural and linguistic differences pose additional hurdles for EFL teachers. Primary students from diverse linguistic backgrounds bring different language structures and concepts to the classroom. Teachers need to be sensitive to these variations and tailor their instructional approaches accordingly. To address this, a study proposes these challenges requires a combination of effective pedagogical strategies, cultural awareness, and adaptability to create an engaging and inclusive learning environment for primary students grappling with the intricacies of the Present Indefinite Tense in English language acquisition.